ANALISIS FAKTOR-FAKTOR KOMPETENSI GURU DALAM MENINGKATKAN KINERJANYA (STUDI KASUS DI SMP MUHAMMADIYAH KOTA KEDIRI) - Heru Sudjatmoko (Universitas Islam Kadiri, 2020)
This study aims to determine the factors competence of teachers to improve their performance in SMP Muhammadiyah Kediri as the case study. Starting from the issue of whether recruitment, competence, and compensation systems affect the performance of teachers. This study will also examine the extent to which factors affect the performance of the principal teacher performance improvement. Based on the above problem, this study aims to determine the factors of teacher competence on performance. In addition, this study also aimed want to know how far the influence of the teacher’s performance on the improvement of school performance. The method used in this study is a survey method explanations (exploration survey method) with a quantitative approach through a causal relationship with path analysis techniques (path analysis). The instrument used to obtain the data is questionnaire. The population of this study is teacher of SMP Muhammadiyah’s in Kediri, research sample as many as 52 people. The results showed that the influence of recruitment, the teacher’s performance of 89.94% contained significant direct influence on performance, and the effect of teacher competence on very high performance is 97.02%. Effect of recruitment, competence, and teacher competence system jointly on the performance of schools 1) 0.05 significant variable recruitment. 2) competence the principal variables significant 0.05. 3) a variable compensation system significantly principals 0.05. The magnitude of the effect of simultaneous variable recruitment, competence, and ststem compensation principals together the school’s performance with 80.1% sign value = 0.001 and 0.037 sig <Alpha - 0.05 then, significantly affect school performance. Important implications for efforts to improve teacher performance in learning. The formulation of the implications of this research emphasis on improving teachers’ perceptions about kompetensiguru; and cultural organizations so as to increase the performance of teachers in learning. With the creation of a good teacher performance is key to improving the quality of education a school because one of the factors that determine the quality of education is determined by the teacher in the educational process. In performing its duties, a teacher not only to master teaching materials, but must have the personality and personal integrity that can be relied upon to be a role model for students, families and communities.